2015
DOI: 10.1186/s12889-015-2132-4
|View full text |Cite
|
Sign up to set email alerts
|

Heterosexual men who patronise entertainment establishments versus brothels in an Asian urban setting – which group practises riskier sexual behaviours?

Abstract: BackgroundSex work has shifted from brothels to entertainment establishments (EEs) in Asia. Men who patronise EEs could act as a bridging population for human immunodeficiency virus (HIV) and sexually transmitted infection (STI) transmission through unprotected sex with the female EE workers to their spouses and regular partners. The aim of this study was to compare the prevalence and factors associated with risky sexual behaviours among the heterosexual men who patronised the EEs and brothels in Singapore.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Notably, IDUs and high-risk heterosexual sex populations might facilitate the recombination of HIV strains that are currently present [ 71 ]. Similarly, our results showed that the proportion of CRF07_BC was an increasing trend since 2007, this likely attributed to the continual activities between heterosexual behaviors and drug use in these areas where the drug trafficking activities are frequent [ 14 , 72 , 73 ], especially for the phenomenon of prostitution to support drug use.…”
Section: Discussionsupporting
confidence: 66%
“…Notably, IDUs and high-risk heterosexual sex populations might facilitate the recombination of HIV strains that are currently present [ 71 ]. Similarly, our results showed that the proportion of CRF07_BC was an increasing trend since 2007, this likely attributed to the continual activities between heterosexual behaviors and drug use in these areas where the drug trafficking activities are frequent [ 14 , 72 , 73 ], especially for the phenomenon of prostitution to support drug use.…”
Section: Discussionsupporting
confidence: 66%
“…Contrarily, the 100% condom use policy is implemented in registered brothels 17 18. Another possible explanation for the low condom usage with paid and casual partners and hence the lack of difference with these partner types is that FEWs are not trained in condom negotiation unlike brothel-based FSWs 19. Condom negotiation has been reported to be a significant predictor of condom use regardless of where the FSWs operate 20 21.…”
Section: Discussionmentioning
confidence: 99%
“…Agents source and recruit these FEWs from overseas for indirect sex work. Although the EE owners do not officially employ them as sex workers, they allow FEWs to solicit in their premises because they attract heterosexual men to patronise the EEs 19. Since the last survey in 2008, sex work in EEs continues to be illegal in Singapore.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, sex work has increasingly shifted from brothels to EEs, particularly in Asia [22]. Heterosexual men patronising EEs who engage in casual or paid sex is an important and yet often neglected at-risk group because these men could potentially act as a bridging population for HIV/STI transmission through unprotected sex to their spouses and regular partners, resulting in extensive transmission to the community [23, 24]. …”
Section: Introductionmentioning
confidence: 99%
“…The percentage of heterosexual Singapore male residents engaging in sexual risk behaviour (defined as having commercial and/or casual sexual exposures) has increased from 4.7% in 1989 [26] to 18.5% in 2007 [27]. One common setting where casual and paid sex takes place in Singapore is in the EEs [23, 24]. Similar to previous years, HIV cases were predominantly males in Singapore, with a male to female ratio of 12:1 in 2014 [28].…”
Section: Introductionmentioning
confidence: 99%